Associations between Dopamine D4 Receptor Gene Variation with Both Infidelity and Sexual Promiscuity - Garcia, Justin R.; MacKillop, James; Aller, Edward L.; Merriwether, Ann M.; Wilson, David Sloan; Lum, J. Koji (PloS one, 2010)
Human sexual behavior is highly variable both within and between populations. While sex-related characteristics and sexual behavior are central to evolutionary theory (sexual selection), little is known about the genetic bases of individual variation in sexual behavior. The variable number tandem repeats (VNTR) polymorphism in exon III of the human dopamine D4 receptor gene (DRD4) has been correlated with an array of behavioral phenotypes and may be predicatively responsible for variation in motivating some sexual behaviors, particularly promiscuity and infidelity. We administered an anonymous survey on personal history of sexual behavior and intimate relationships to 181 young adults. We also collected buccal wash samples and genotyped the DRD4 VNTR. Here we show that individuals with at least one 7-repeat allele (7R+) report a greater categorical rate of promiscuous sexual behavior (i.e., having ever had a "one-night stand") and report a more than 50% increase in instances of sexual infidelity. DRD4 VNTR genotype varies considerably within and among populations and has been subject to relatively recent, local selective pressures. Individual differences in sexual behavior are likely partially mediated by individual genetic variation in genes coding for motivation and reward in the brain. Conceptualizing these findings in terms of r/K selection theory suggests a mechanism for selective pressure for and against the 7R+ genotype that may explain the considerable global allelic variation for this polymorphism.